Developing a Social Media Marketing Plan for Sky Technology and Solutions Company limited - Huynh, Thi Luu (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Digital Marketing; 2021-2025.